2019
DOI: 10.7181/acfs.2019.00346
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of violence in pediatric and adolescent nasal fracture compared with adult nasal fracture: An 8-year study

Abstract: Background The epidemiology of nasal fractures varies according to factors such as the era and area of the study, as well as the age of the patient. We compared the characteristics and causes of pediatric nasal fractures. Methods A total of 2,321 patients with nasal fractures from 2010 to 2017 were examined. The patients were divided into age groups using the Korean school system of age classification. The causes of injury were divided into five groups: violence, fall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In the hospital, which is in the South-Eastern region of Turkey, falls were the most common etiology in patients who underwent SA and TA; whereas assault was the most common cause in the IA group. In prior studies, it had been reported that assault and motor accident-related cases were more common in adults, while falls were more common in children [13]. In our study, operation time was longer in the SA group with a [14] and time between injury and operation was longer in the SA than IA and TA with 3.9±2.1 days in this study (p<0.05).…”
Section: Discussionsupporting
confidence: 60%
“…In the hospital, which is in the South-Eastern region of Turkey, falls were the most common etiology in patients who underwent SA and TA; whereas assault was the most common cause in the IA group. In prior studies, it had been reported that assault and motor accident-related cases were more common in adults, while falls were more common in children [13]. In our study, operation time was longer in the SA group with a [14] and time between injury and operation was longer in the SA than IA and TA with 3.9±2.1 days in this study (p<0.05).…”
Section: Discussionsupporting
confidence: 60%
“…For this reason, interpersonal violence has shown to relatively increase as an important cause [8][9][10]. In recent studies, the most frequent cause of injury was assault, followed by falls, sport accidents, TA, work accidents, and other causes [11]. In this study, the most common injury mechanism was in the order of TA, falls, work accidents, and assault.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies of pediatric nasal fractures have investigated the incidence, etiology, treatment options, and outcomes [3,[6][7][8], but few reports have analyzed the time interval between in-…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of pediatric nasal fractures have investigated the incidence, etiology, treatment options, and outcomes [ 3 , 6 - 8 ], but few reports have analyzed the time interval between injury and reduction or presented objective results based on computed tomography (CT) images of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%